Nutrient's Games: Evaluating the Impact of Interactive Media on Improving Nutrition Knowledge Among Students - Soesanto, Muhammad Ravi Maulana; Halizah, Amilatun Nur; Risky, Aulia Dwi Nur; Yuliasari, Elly; Kharisma, Fian Ninda; Inayah, Nafisah Widhah; Setianingsih, Nida Nabilah (Tarqabin Nusantara Group, 2024)
Child nutrition is important for children's physical and cognitive development. However, many children do not have a good understanding of child nutrition. Interactive media has the potential to be an effective tool to teach children about child nutrition. This study aims to determine the effectiveness of interactive media (Game Nutrient`s Pocket) in improving students understanding of child nutrition. This study used a pre-experimental research design with a one-group pretest-posttest design. The participants of this study were a group of grade 1 to grade 5 elementary school students at SDN Kedungpedaringan II Kepanjen, Indonesia. The results showed that there was a significant difference in students understanding of child nutrition between the pretest and posttest. This means that the use of interactive media (Game Nutrient`s Pocket) can improve students understanding of child nutrition. The findings of this study have important implications for the use of interactive media in education. Interactive media can be used to develop educational games and simulations that can help students to learn about various topics, including child nutrition. Based on the results of the study, it can be concluded that the Nutrient`s Pocket Game can improve the nutritional knowledge of students of SDN Kedungpedaringan II Kepanjen. This game can be an alternative learning media for nutrition that is effective and interesting for students.